Dietary quality, lifestyle factors and healthy ageing in Europe: the SENECA study - Haveman‐Nies, Annemien; de Groot, Lisette C.P.G.M.; van Staveren, Wija A. (Age and ageing, 2003)
Objective:  to identify dietary and lifestyle factors that contribute to healthy ageing. Subjects:  for the analyses, data of the longitudinal SENECA study were used. The study population consisted of 1091 men and 1109 women aged 70–75 years from Belgium, France, Denmark, Italy, The Netherlands, Portugal, Spain, Switzerland, and Poland. Methods:  this European study started with baseline measurements in 1988–1989 and lasted until 30 April 1999. The study includes data on diet, lifestyle and health. The study population is followed for 10 years, and measurements were performed in 1988/1989 (baseline), 1993, and 1999. The relationships of the three lifestyle factors diet, physical activity, and smoking habits to survival and maintenance of health at old age were investigated. Finally it is discussed whether the relationships of healthy lifestyle habits to survival and health contribute to healthy ageing. Results:  the unhealthy lifestyle habits smoking, having a low‐quality diet, and being physically inactive were singly related to an increased mortality risk (hazard ratios ranged from 1.2 to 2.1). In addition, inactive and smoking persons had an increased risk for a decline in health status as compared with active and non‐smoking people. The net effect of a healthy lifestyle on the process of healthy ageing is likely to go together with a compressed cumulative morbidity. Conclusions:  a healthy lifestyle at older ages is positively related to a reduced mortality risk and to a delay in the deterioration in health status. This postponement of the onset of major morbidity is likely to go together with a compressed cumulative morbidity. Therefore, health promotion at older ages can contribute to healthy ageing.